The Effect of Learning Motivation and Learning Discipline on Student Learning Achievement - Puspasari, Durinta; Muyassaroh, Jazi' (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effect of learning motivation and learning discipline on student achievement of class XII OTKP in Automation of Public Relation and Protocol at SMK PGRI 2 Sidoarjo. This study uses a quantitative approach. This type of research uses explanatory research. Primary data comes from questionnaires, while secondary data comes from school data, books, and journals. The population in this study were all students in class XII OTKP at SMK PGRI 2 Sidoarjo, totaling 98 students. This study uses a census or total sampling because the total population is less than 100, namely 98 students. The data collection techniques use questionnaires, documentation, and interviews. The data analysis techniques used the normal test, homogeneity test, t-test, F-test, and coefficient of determination (R2). The results of this study indicate that there is an influence of learning motivation on student achievement, an influence of learning discipline on student achievement, and an influence of learning motivation and learning discipline on student achievement. Suggestions for future researchers are expected to add other variables that affect learning achievement.